Contemporary business mathematics for colleges - Deitz, James E. (Thomson South-Western, 2006)
This briefer version of the best-selling CONTEMPORARY BUSINESS MATH FOR COLLEGES presents an arithmetic-based, basic approach to business math. It emphasizes a practical, skill building approach to prepare students for future careers in business through step-by-step development of concepts, numerous practice exercises throughout, and a focus on real-world application of techniques. The text progresses from the most basic to more complex business math topics